Bronchial brush cytology of primary anaplastic large cell lymphoma of lung. Issue 9 (16th April 2018) - Rajagopal, Meyyappa Devan; Gochhait, Debasis; Hanuman Srinivas, Bheemanathi; Ganesh, Rajesh Nachiappa; Siddaraju, Neelaiah; Rajaram, Manju
Abstract : Primary pulmonary lymphoma is defined as clonal lymphoid proliferation affecting one or both lungs in a patient with no extrapulmonary involvement at the time of diagnosis or during the subsequent 3 months. Anaplastic large cell lymphoma (ALCL) is a rare T‐cell neoplasm which occurs as two distinct clinical entities—cutaneous and systemic variant. Primary lung involvement is extremely uncommon. It can be classified on the basis of being positive or negative for ALK rearrangement which carries prognostic significance. The 2016 revision of World Health Organization (WHO) classification of lymphoid neoplasm recognizes three types of ALCL namely ALK‐positive, ALK‐negative, and breast implant associated. Here, we report a case of primary pulmonary ALK‐1 positive ALCL which was initially recognized in bronchial brushing cytology based on distinct morphologic clues.